A “Push–Pull” Stabilized Phosphinidene Supported by a Phosphine‐Functionalized β‐Diketiminato Ligand - Bestgen, Sebastian (Chemistry, 2020)
The use of a bis(diphenyl)phosphine functionalized β‐diketiminato ligand, [HC{(CH(3))C}(2){(ortho‐[P(C(6)H(5))(2)](2)C(6)H(4))N}(2)](−) (PNac), as a support for germanium(II) and tin(II) chloride and phosphaketene compounds, is described. The conformational flexibility and hemilability of this unique ligand provide a versatile coordination environment that can accommodate the electronic needs of the ligated elements. For example, chloride abstraction from [(PNac)ECl] (E=Ge, Sn) affords the cationic germyliumylidene and stannyliumylidene species [(PNac)E](+) in which the pendant phosphine arms associate more strongly with the Lewis acidic main group element centers, providing further electronic stabilization. In a similar fashion, chemical decarbonylation of the germanium phosphaketene [(PNac)Ge(PCO)] with tris(pentafluorophenyl)borane affords a “push–pull” stabilized phosphinidene in which one of the phosphine groups of the ligand backbone associates with the low valent phosphinidene center.